2016
DOI: 10.1177/0300985815618436
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Features of Colorectal Inflammatory Polyps in Miniature Dachshunds

Abstract: The histopathologic characteristics of colorectal inflammatory polyps that formed in Miniature Dachshunds were compared with those of other colorectal proliferative lesions, including adenomas and adenocarcinomas. Fifty-three colorectal polypoid lesions were histopathologically classified into inflammatory polyps (26 cases), adenoma (18 cases), and adenocarcinoma (9 cases). All 26 dogs that were diagnosed with inflammatory polyps were Miniature Dachshunds, indicating that colorectal inflammatory polyps exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…The age and location of polypoid lesions in the present Jack Russell terrier cases were similar to those reported in human FAP 22,24,26 ; however, the high incidence of gastric tumors may be a characteristic unique to the breed of Jack Russell terriers. In contrast, the large intestine is of importance, while considering the tumorigenesis of gastrointestinal tumors in Miniature Dachshunds because the breed frequently develops inflammatory polyposis in the colorectum 27,28 . A previous study, by the authors, showed that inflammatory polyposis in Miniature Dachshunds may subsequently develop into adenoma or adenocarcinoma 29 adenocarcinoma, papillary adenocarcinoma, mucinous adenocarcinoma, signet-ring cell carcinoma, undifferentiated carcinoma and adenosquamous carcinoma 3 .…”
Section: Histopathological Classification Of Intestinal Tumorsmentioning
confidence: 99%
“…The age and location of polypoid lesions in the present Jack Russell terrier cases were similar to those reported in human FAP 22,24,26 ; however, the high incidence of gastric tumors may be a characteristic unique to the breed of Jack Russell terriers. In contrast, the large intestine is of importance, while considering the tumorigenesis of gastrointestinal tumors in Miniature Dachshunds because the breed frequently develops inflammatory polyposis in the colorectum 27,28 . A previous study, by the authors, showed that inflammatory polyposis in Miniature Dachshunds may subsequently develop into adenoma or adenocarcinoma 29 adenocarcinoma, papillary adenocarcinoma, mucinous adenocarcinoma, signet-ring cell carcinoma, undifferentiated carcinoma and adenosquamous carcinoma 3 .…”
Section: Histopathological Classification Of Intestinal Tumorsmentioning
confidence: 99%
“…The 8 MDs with ICRPs had been referred to Hokkaido University Veterinary Teaching Hospital for the investigation of hematochezia, tenesmus and an increased frequency of defecation and diagnosed with ICRPs based on clinical and histopathological findings of a previous report [13, 20]. They consisted of 5 males (2 intact and 3 neutered) and 3 females (2 intact and 1 neutered), and the median age of these dogs was 10 years (range, 9 to 14 years).…”
Section: Methodsmentioning
confidence: 99%
“…These 5 MDs consisted of 2 neutered males and 3 females (1 intact and 2 neutered), and the median age of these dogs was 9 years (range, 8 to 11 years). Inflamed mucosal lesions were staged (I-III) according to criteria adapted from those described previously [20]. Lesions in which >15, 5 -15 and <5% of the tissue consisted of epithelial cells were defined as stages I, II and III lesions, respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CK expression of Barrett’s esophagus is characterized by diffuse CK7 staining and surface staining of CK20 14 , which were also observed in the present canine case. CK20 is a marker of differentiated intestinal epithelial cells, and its expression is decreased in the esophageal and intestinal adenocarcinoma cells of humans and dogs 15 , 16 .…”
mentioning
confidence: 99%